Economic evaluation of routine infant rotavirus immunisation program in Japan - Shu-ling Hoshi; Masahide Kondo; Ichiro Okubo (Taylor & Francis Group, 2017)
Two rotavirus vaccines are currently available in Japan. We estimated the incremental cost-effectiveness ratio (ICER) of routine infant rotavirus immunisation program without defining which vaccine to be evaluated, which reflects the current deliberation at the Health Science Council in charge of Immunisation and Vaccine established by the Ministry of Health, Labor and Welfare of Japan. Three ICERs were estimated, one from payers' perspective and 2 from societal perspective depending on the scenarios to uptake vaccines. The health statuses following the birth cohort were as follows: not infected by rotavirus, asymptomatic infection, outpatients after infection, hospitalised after infection, developing encephalitis/encephalopathy followed by recovery, sequelae, and death. Costs of per course of vaccination was ¥30,000 (US$283; US$1 = ¥106). The model runs for 60 months with one month cycle. From payers' perspective, estimated ICERs were ¥6,877,000 (US$64,877) per QALY. From societal perspective, immunisation program turns out to be cost-saving for 75% simultaneous vaccination scenario, while it is at ¥337,000 (US$3,179) per QALY gained with vaccine alone scenario. The probability of rotavirus immunisation program to be under ¥5,000,000 (US$47,170) per QALY was at 19.8%, 40.7%, and 75.6% when costs per course of vaccination were set at ¥30,000 (US$283), ¥25,000 (US$236), and ¥20,000 (US$189), respectively. Rotavirus immunisation program has a potential to be cost-effective from payers' perspective and even cost-saving from societal perspective in Japan, however, caution should be taken with regard to the interpretation of the results as cost-effectiveness is critically dependent on vaccination costs.